2014
DOI: 10.1038/onc.2014.364
|View full text |Cite
|
Sign up to set email alerts
|

Cks1 is a critical regulator of hematopoietic stem cell quiescence and cycling, operating upstream of Cdk inhibitors

Abstract: Cyclin-dependent kinase subunit 1 (Cks1) is a critical rate-limiting component of the Skp1-Cullin1-Skp2 (SCF(Skp2)) ubiquitin ligase that controls cell cycle inhibitor abundance. Cyclin-dependent kinase (Cdk) inhibitors (CKIs) regulate hematopoietic stem cell (HSC) self-renewal, regeneration after cytotoxic stress and tumor cell proliferation. We thus studied the role of Cks1 in HSC and in a prototypic stem cell disorder, chronic myeloid leukemia (CML). Cks1 transcript was highly expressed in Lin-Sca-1+Kit+ (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…These data are in agreement with publicly available datasets, including the MILE study [46] , which also found significantly higher CKS1B and CKS2 expression in healthy bone marrow mononuclear cells compared to bulk MLLr leukaemic samples. Altogether, these analyses revealed a dysregulation of CKS expression in MLLr leukaemia, but also in BCR-ABL positive CML [47] , consistent with putative roles for CKS1B and CKS2 in leukaemogenesis. CKS expression levels might also be linked to the relative stage of maturation in normal haematopoiesis (CD34 + versus PBMC).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…These data are in agreement with publicly available datasets, including the MILE study [46] , which also found significantly higher CKS1B and CKS2 expression in healthy bone marrow mononuclear cells compared to bulk MLLr leukaemic samples. Altogether, these analyses revealed a dysregulation of CKS expression in MLLr leukaemia, but also in BCR-ABL positive CML [47] , consistent with putative roles for CKS1B and CKS2 in leukaemogenesis. CKS expression levels might also be linked to the relative stage of maturation in normal haematopoiesis (CD34 + versus PBMC).…”
Section: Resultssupporting
confidence: 69%
“…Previous studies, describing the requirement of Cks1 [8] , [47] and Cks2 [8] , [13] in cell cycle dynamics, have postulated that targets of the Cks1/Cks2 axis may extend beyond the specific subset of Cyclins and CKIs [5] , [7] , [10] , [13] , [62] . Here, we provide the first evidence for an essential role of the Cks1/Cks2 axis in the regulation of Mll1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Surface markers were stained using antibodies from eBioscience (eBioscience Natutec, Heidelberg Germany, http://www.ebioscience.com), except for PE‐Cy5.5‐streptavidin conjugate, which was obtained from Invitrogen (Thermo Fischer, Karlsruhe, Germany, https://www.thermofisher.com) as previously described (Supporting Information Table S1) . For bone marrow staining, 2 × 10 6 cells were used for mature population stains, and 6 × 10 6 for staining of progenitors and HSCs.…”
Section: Methodsmentioning
confidence: 99%
“…The data from this work also shows that YM-155 mediates a loss in (budding uninhibited by benzimidazoles 1) BUB1 [-5.95, p<0.001]/BUB1B which could block not only checkpoint activity leading to mitosis but also spindle assembly, kinetochore-microtubule attachment and chromosome segregation (88,108,109). Other related transcripts down-regulated by YM-155 include SKP2 [-2.23, p<0.001] which encodes for S-phase kinase-associated protein 2 which is part of SCF complex (SKp1-cullin-FBox)/ Cks1 inversely associated with concentration of p27Kip1 and p57Kip2 (CDK inhibitors) which initiate cell cycle arrest (110,111).…”
Section: Discussionmentioning
confidence: 99%